Experimental and simulation study on the aerodynamic performance of a counter rotating vertical axis wind turbine - Didane, Djamal Hissein (2017)
The Darrieus H-rotor has gained much interest in the last few decades as among the reliable devices for wind energy conversion techniques, for their relatively simple structure and aerodynamic performance. In the present work, development and aerodynamic performance predictions of a unique contra-rotating VAWT have been studied through experimental and computational approaches as it has yet to be applied to a VAWT. The main purpose of this study is to develop and investigate the practicality of employing the contra-rotating concept to a VAWT system while enhancing its conversion efficiency. The simulation study was performed using three-dimensional computational fluid dynamics (CFD) models based on K-omega shear stress transport (SST) model. The computational work covers a wider range of simulation processes compared to the experiment which includes a parametric study based on the axial distance between the two rotors and blade height. The performance evaluations of the current models were established in terms of key aerodynamic parameters such as torque and power. The systematic analysis of these quantities showed the usefulness of the contra-rotating technique on a VAWT system and the ability to extract additional more than threefold power over the entire operating wind speeds covered. The system has also improved the inherent difficulties of the Darrieus rotor to self-start. The results also demonstrated a significant increase in terms of conversion efficiency for both power and torque compared to a single-rotor system of a similar type. A maximum of 43% and 46% of power and torque coefficients were respectively possible with the current dual-rotor system. The simulation results indicate that smaller axial distance tends to enhance the performance output of the system relatively better compared to a larger distance. However, in terms of the blade height, longer blades generated the highest amount of power. It is anticipated that this current technique could revolutionize wind energy harvesting strategies and would find applications in a wide range of sites that are characterized by low and moderate wind regimes and particularly be useful in the urban environment where turbulence is high.